Sexual Functions in Obsessive Compulsive Disorder Patients: A Case Report - Nergis LAPSEKÝLÝ; Elif TEMÝZSU; Mehmet AK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: Obsessive-compulsive disorder (OCD), even if the patient’s obsession content is not related to sexuality, may be a problem in the sexual lives of individuals. In this article, sexual function in obsessive compulsive disorder patients is discussed based on an OCD case. Case: Male 36 years old and female 32 years old couple. Man had complaints of lack of control of ejaculation and woman had complaints of lack of orgasm. Man was diagnosed with premature ejaculation and woman was diagnosed with aversion and anorgasmia according to DSM-IV (Diagnostic and Statistical Manual Of Mental Disorders) criteria. During therapy, the female patient was diagnosed with OCD as well. Loss of control was not acceptable to the patient. Thus she was avoiding from exhilarating stimuli. After cognitive restructuring of her evaluations about control, sex therapy was continued. At the end of the therapy the avoidance of the patient disappeared and anorgasmia was treated and ejeculation time of the male patient was 15 minutes. Conclusion: Sexual dysfunction is a common problem in patients with OCD. Patient may have avoidance that may adversely affect her sexuality. If a patient has avoidance about sexuality, the reason of this avoidance may or may not be the usual and expected thought content like avoidance of contamination. The evaluations of OCD patients about control may also adversely affect their sexuallity. The thought leading to avoidance behavior, may vary from patient to patient. However, to identify these thoughts with cognitive interventions and work with them will improve.the patient.